2021
DOI: 10.3390/ijerph18020671
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Changes in Physical Activity and the Relation to Life Satisfaction and Rated Physical Capacity in Swedish Adults during the COVID-19 Pandemic—A Cross Sectional Study

Abstract: COVID-19 restrictions may prevent people from reaching recommended levels of physical activity (PA). This study examines self-perceived changes in the extent and intensity of PA during the COVID-19 pandemic, and the relation between perceived changes in PA and general life satisfaction and perceived physical capacity. A total of 1318 participants (mean age 47.8 SD12.6; 82.1% women) were recruited through social media in Sweden during autumn 2020. The survey included questions regarding perceived changes in PA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 33 publications
3
65
4
Order By: Relevance
“…In contrast, findings are less consistent with regard to sex and age. Notwithstanding, interestingly, the reported magnitude of PA reductions here (41% to 42%) and guideline compliance declines (18.5%) was larger than reported from other surveys [16][17][18][19][20].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In contrast, findings are less consistent with regard to sex and age. Notwithstanding, interestingly, the reported magnitude of PA reductions here (41% to 42%) and guideline compliance declines (18.5%) was larger than reported from other surveys [16][17][18][19][20].…”
Section: Discussioncontrasting
confidence: 67%
“…To date, the degree to which public life restrictions related to COVID-19 affect PA levels is unknown. Early evidence based on investigations with relatively small sample sizes, however, indicate reductions of PA [16][17][18][19][20]. The present study, therefore, aimed to evaluate changes of self-reported PA in countries with SARS-CoV2 outbreaks on a multinational level.…”
Section: Introductionmentioning
confidence: 95%
“…For example, recent work studying youth long-distance runners found that COVID-19 social distancing restrictions impacted training habits (Bazett-Jones et al, 2020 ). Furthermore, recent studies have illustrated that physical activity levels during the COVID-19 global pandemic have decreased (Castañeda-Babarro et al, 2020 ; Gallè et al, 2020 ; Eek et al, 2021 ; Fearnbach et al, 2021 ; Puccinelli et al, 2021 ; Wilke et al, 2021 ). Self-reported moderate physical activity levels have been reported to decrease by 41%, while Eek and colleagues depicted that more than 65% of the participants reported changes in their physical activity (Eek et al, 2021 ; Wilke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have illustrated that physical activity levels during the COVID-19 global pandemic have decreased (Castañeda-Babarro et al, 2020 ; Gallè et al, 2020 ; Eek et al, 2021 ; Fearnbach et al, 2021 ; Puccinelli et al, 2021 ; Wilke et al, 2021 ). Self-reported moderate physical activity levels have been reported to decrease by 41%, while Eek and colleagues depicted that more than 65% of the participants reported changes in their physical activity (Eek et al, 2021 ; Wilke et al, 2021 ). Such forced changes from a known, habitual lifestyle to novel pandemic restrictions provided a unique scenario to investigate how new environmental, social, and psychological barriers influence running behaviors and RRI risk in a large sample.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that regular exercise increases the life expectancy and quality of life even in people who did not do regular physical activity until old age. Physical activity levels in the pandemic have decreased significantly due to staying at home and this will cause an increase in the risk of many secondary diseases [41,57,43]. Poor food intake and food insecurity caused mental health to be affected in the elderly and caused the development of depression [47].…”
Section: Increasedmentioning
confidence: 99%